PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVb SD NEGERI 067 TEGAR - Situmorang, Rudianto; Sakur, Sakur; Roza, Yenita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve mathematics learning outcomes in SD Negeri 067Tegar by implementing cooperative learning model Two Stay Two Stray (TSTS) structural approach. Subjects of the research were students grade IVb whohave the academic ability of the heterogeneous. This research is classroom action research with two cycles. Each cycles has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score. Results of this research indicate that the application of Cooperative Learning Model Two Stay Two Stray (TSTS) Structural Approach can improve the mathematics learning outcomes of students grade IVb SD Negeri 067 Tegar Pematang Pudu in the first semester academic year 2013/2014.Key words: Mathematics learning outcomes, Cooperative learning, Two Stay Two Stray (TSTS), Classroom action research.WISUDA OKTOBER